ANALISIS LENDUTAN STRUKTUR PERKERASAN KAKU AKIBAT PENGARUH KADAR AIR TANAH DASAR - Hendra Wahyu; Suherman Sulaiman; Mujiman Mujiman (Potensi: Jurnal Sipil Politeknik, 2018)
The research attempts to find the deflection on a concrete slab that functions as a layer on top of a rigid pavement, the strain occurring on the pulling part as an effect of subgrade water, and the effects of static quasi loads in the middle of the concrete slab. The research adopted the experimental method with a testing object of concrete slab with a size of 1.0 x 1.0 x 0,1 m placed on top of lean concrete layer and subgrade with the size of 1.0 x 1.0 x 0,035 m and 1.0 x 1.0 x 0.4 m, respectively. Quasi-static loads were placed upon 3 (three) variations of tested objects. Variation 1 is the placing of loads on top of a concrete slab with 30% water content of the subgrade dry weight; variation 2 is the placing of loads on top of a concrete slab with 40% water content of the subgrade dry weight; and variation 3 the placing of loads on top of a concrete slab with 50% water content of the subgrade dry weight. The findings show that the carrying capacity of the concrete slab decreases. Th maximum carrying capacities of the concrete slab were 82.5 kN, 62.33 kN, and 30.06 kN for variation 1, variation 2, and variation 3, respectively.